Facile synthesis of functionalized spiro[indoline-3,2'-oxiran]-2-ones by Darzens reaction - Fu, Qin; Yan, Chao-Guo (Beilstein Journal of Organic Chemistry, 2013)
A series of functionalized spiro[indoline-3,2'-oxiran]-2-ones was efficiently synthesized by Darzens reaction of phenacyl bromides with isatins both with N-alkyl groups and without N-substituent in the presence of potassium carbonate as a base catalyst. When two equivalents phenacyl bromides were used in the reaction, the N-substitution reaction of isatin also finished with the formation of spiro-oxirane-oxindoles.
Keywords: Darzens reaction; isatin; oxindole; oxirane; spiro-epoxyoxindole; spirooxindole